Seismic Performance of Fully Prefabricated L-Shaped Shear Walls with Grouted Sleeve Lapping Connectors under High Axial Compression Ratio - Qiong Yu; Ziming Tang; Xingkui Zhang; Baoxiu Fan; Zhi Zhang; Zhenhai Chen (Applied Sciences, 2023)
The grouted sleeve lapping connector called the APC connector has the advantages of high fault tolerance, convenient construction, compacted grouting, and low cost, together with realizing full prefabrication of vertical components. In this paper, a quasi-static test of two fully prefabricated L-shaped walls connected with two types of APC connector and a cast-in-place wall was carried out under high axial compression ratio (0.5) to compare their seismic performance. The results indicated that the two types of connectors effectively transferred the rebar stress in the prefabricated walls, and the failure modes and final crack distribution of the prefabricated walls and the cast-in-place wall were basically identical. The failure of the cast-in-place wall occurred at the root of the wall limb, while the failure of the prefabricated walls occurred at the top of the sleeve due to the constraint of the sleeve. The bearing capacity, stiffness, ductility, and energy dissipation of the prefabricated specimen connected by the type-I sleeve was comparable to that of the cast-in-place wall, while the prefabricated wall connected by the type-II sleeve showed greater bearing capacity, stiffness, and ductility. Finally, some suggestions for seismic design of prefabricated components connected with APC connectors are proposed.